Pelaksanaan Kurikulum Merdeka dalam Pembelajaran Bahasa Jawa di SMP Kabupaten Pemalang - Nurfita, Dwi; Sukoyo, Joko (PAKAR Pendidikan, 2024)
Curriculum changes require adjustments to learning in schools, including Javanese language learning. The implementation of Javanese language learning, which is a local content subject, has been implemented at junior high school level in Pemalang Regency. In its implementation, there needs to be supervision from various related parties. Therefore, this research aims to describe the implementation of the independent curriculum in Javanese language learning in Pemalang Regency and the difficulties in implementing the independent curriculum. The method used is descriptive qualitative by collecting observation data and interviews with Javanese language teachers in Pemalang Regency. The results of the research obtained are that the implementation of the independent curriculum in junior high school Javanese language learning in Pemalang Regency has been running in grade 7. The adjustments that have occurred include changes in learning tools, implementation of student-centered learning, learning assessments carried out in the form of diagnostic, formative and summative assessments as well as project activities (P5). Difficulties experienced by teachers, such as teachers' understanding of the concept of an independent curriculum which affects teachers' abilities in compiling learning tools, lack of references or benchmarks in preparing teaching modules, selection and use of media and learning methods, as well as teachers' understanding of the concept of independent curriculum assessment.